Superior mesenteric artery syndrome: A review of the literature - Jasmin England; Natasha Li (Journal of the American College of Emergency Physicians Open)
Abstract Decreased intraabdominal fat can lead to intraabdominal compressive syndromes, such as superior mesenteric artery (SMA) syndrome. This phenomenon is rare but should be considered in a patient with recent rapid weight loss and acute gastrointestinal complaints. A delay in diagnosis and treatment can lead to severe complications, such as a gastric rupture. We report a case of SMA syndrome in a teenage male with recent intentional weight loss and intractable emesis, and the possible associations of SMA syndrome and Nutcracker syndrome.